KINERJA ORGANISASI KANTOR UNIT PENYELENGGARA PELABUHAN KELAS III SAPE PROVINSI NUSATENGGARA BARAT - Rahman, Irwan; Nurmiati, Nurmiati; Diana, Fina (Patria Artha University, 2022)
This study aims to explain the organizational performance of the Class III Sape Port Operator Unit Office, West Nusatenggara Province. The data analysis technique used is a quantitative descriptive method, which describes the results of questionnaires and interviews obtained. The results showed that the organizational performance of the Sape Class III Port Operator Unit Office with an average score of 2.94 or was in the good enough category where the highest average score was on the accountability indicator, which was 3.18 or was in the good enough category while the lowest score lies in the service quality indicator, which is 2.66 or is in the fairly good category.